A hyaluronic acid–pentamidine bioconjugate as a macrophage mediated drug targeting delivery system for the treatment of leishmaniasis. Issue 116 (5th November 2015) - Micale, N.; Piperno, A.; Mahfoudh, N.; Schurigt, U.; Schultheis, M.; Mineo, P. G.; Schirmeister, T.; Scala, A.; Grassi, G.
Abstract : A new HA–Pent bioconjugate was synthetized and proposed as drug targeting delivery system for the treatment of leishmaniasis, exploiting the specific biological recognition of HA by the macrophage. Abstract : Leishmaniasis is still a serious public health problem worldwide, especially in tropical areas where this infectious disease is endemic. The most severe form of the disease ( i.e. visceral) can claim victims if left untreated and the few accessible drugs have several drawbacks including major side effects and parenteral administration. In this context, the investigation of new delivery modalities which might reduce the toxicity and increase the bioavailability of the drugs currently on the market represents a valid strategy to counter these problems. Herein we present the development of a macrophage mediated drug targeting delivery system by conjugating the anti-leishmanial drug pentamidine (Pent) with the biocompatible polymer hyaluronic acid (HA), the latter employed at the same time as a delivery platform and targeting scaffold. Biological assays against Leishmania major amastigote-infected macrophages and primary bone marrow derived macrophages (BMDM) confirmed the validity of our strategy as the resulting bioconjugate HA–Pent increased both the potency and the selectivity index of the drug.